Training needs assessment of intensive care nurses in Zabol University of Medical Sciences' Hospitals - Javad Vatani; Shima Javadifar; Mohammad Ali Shahabi Rabori; Zahra Khanikosarkhizi; Tayebeh Ilaghinezhad Bardsirii; Ehsan Mazloumi; Naser Dehghan; Ali Sadeghi Moghaddam; Alireza Khammar; Mehdi Raei (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The improvement of the knowledge, skill, and attitude of nurses working at the intensive care unit (ICU) through implementing training need assessment and holding continuous in-service training courses are of main requisites for providing better health services to the community. Based on this, in the present work, we are looking for the identification and prioritization of the training need of intensive care nurses in the Zabol University of Medical Sciences' hospitals. MATERIALS AND METHODS: As a cross-sectional, descriptive study, including two phases of identification and prioritization of training needs of ICU nurses, it was conducted by a close-ended researcher-made questionnaire for collecting the data on training needs from the viewpoint nursing officials, supervisors, and head nurses of the ICU wards in the first phase and a multiple-choice scientific test plus a checklist for measuring the knowledge and skill of the nurses in the ICU in the second phase. In both phases, census method was used for collecting the data. The validity and reliability of data-gathering tools, mentioned above, were tested and verified before gathering data. Data were analyzed with the descriptive statistics. RESULTS: The results indicated that ventilator setting according to arterial blood gas sampling and interpretation (77.81), cardiac monitoring, detecting dysrhythmia and taking immediate intervention (73.04), ventilator setting according to patient's respiratory status (68.61), airway management, oxygenation and intubation (64.39), and adults cardiopulmonary resuscitation (61.77) were the high-priority training needs of the nurses successively. CONCLUSION: To improve the quality of training programs and upgrading the knowledge, skill, and attitude of nurses working at ICU, the significance and the weight of each training titles should be determined according to the standards and the continuous in-service training plan along with nurses' training needs and duties.